Racial/ethnic differences in healthcare visits made prior to suicide attempt across the United States - Ahmedani, Brian K. (Med Care, 2015)
BACKGROUND: Suicide is a public health concern, but little is known about the patterns of healthcare visits made before a suicide attempt, and whether those patterns differ by race/ethnicity. OBJECTIVES: To examine racial/ethnic variation in the types of healthcare visits made before a suicide attempt, when those visits occur, and whether mental health or substance use diagnoses were documented. RESEARCH DESIGN: Retrospective, longitudinal study, 2009–2011. PARTICIPANTS: 22,387 individuals who attempted suicide and were enrolled in the health plan across 10 health systems in the Mental Health Research Network. MEASURES: Cumulative percentage of different types of healthcare visits made in the 52-weeks before a suicide attempt, by self-reported racial/ethnicity and diagnosis. Data were from the Virtual Data Warehouse at each site. RESULTS: Over 38% of individuals made any healthcare visit within the week before their suicide attempt and ~95% within the preceding year; these percentages varied across racial/ethnic groups (p<0.001). White individuals had the highest percentage of visits (>41%) within 1-week of suicide attempt. Asian Americans were the least likely to make visits within 52 weeks. Hawaiian/Pacific Islanders had proportionally the most inpatient and emergency visits before an attempt, but were least likely to have a recorded mental health or substance use diagnosis. Overall, visits were most common in primary care and outpatient general medical settings. CONCLUSIONS: This study provides temporal evidence of racial/ethnic differences in healthcare visits made prior to suicide attempt. Healthcare systems can use this information to help focus the design and implementation of their suicide prevention initiatives.